2002
DOI: 10.1002/1521-3765(20020215)8:4<876::aid-chem876>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Molecular Dumbbells into Organized Bundles with Tunable Size

Abstract: Dumbbell-shaped molecules consisting of three biphenyls connected through vinyl linkages as a conjugated rod segment and aliphatic polyether dendritic wedges with different crosssections (i.e., dibranch (1), tetrabranch (2) and hexabranch (3)) were synthesized and characterized. The molecular dumbbells self-assemble into discrete bundles that organize into three-dimensional superlattices. Molecule 1, based on a dibranched dendritic wedge, organizes into primitive monoclinic-crystal-line and body-centered, tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 29 publications
4
50
1
Order By: Relevance
“…We have seen how studies of 3D thermotropic phases led to the opening of an entirely new field of soft and nanoscale (14) [47], (c) [65], (d) (27) [18], (e) (16) [10], and (f) [13].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have seen how studies of 3D thermotropic phases led to the opening of an entirely new field of soft and nanoscale (14) [47], (c) [65], (d) (27) [18], (e) (16) [10], and (f) [13].…”
Section: Resultsmentioning
confidence: 99%
“…Lee et al [14] synthesized three dumbbell-shaped compounds having a rodlike conjugated core consisting of three biphenyls connected via vinylene groups. An aliphatic ether dendron group was attached at each end.…”
Section: Body-centered Tetragonal Phase In Rod-coil Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13][14] It has been reported that ordered nanostructures can be precisely controlled by rod-coil block systems which self-assemble into lamellar, cylindrical, and discrete nanostructures depending on the relative volume fraction of the rod or coil segment. [15][16][17][18][19] Molecules based on a conjugated rod building block, which have unique optical and electronic properties, are of great interest due to the physical properties of these molecules or polymers and are dramatically influenced by the creation of their wellordered diverse supramolecular nano-structures. 4,8,20 Lee and coworkers have reported synthesis and electro-optical studies of self-organizing coil-rod-coil triblock molecules consisting of three biphenyls connected through vinylene linkages as a conjugated rod segment and poly(propylene oxide) (PPO) as the coil segment (molecules 9 and 10 see Scheme I).…”
Section: Introductionmentioning
confidence: 99%
“…When the π -conjugated rods are incorporated into the rod-coil block molecules, their photophysical properties are associated, to a large extent, with their self-assembling nanostructure and microscopic morphology on solid supports [8][9][10][11][12]. It has been confirmed that the self-assembling structure and microscopic morphology of rod-coil block molecules on solid supports are not only related to the molecular composition and the block ratio, which determine the nanostructure of rod-coil molecules in solution and bulk state [13][14][15], but also related to the preparation condition of thin films [16][17][18]. However, a comprehensive understanding of the self-assembling behaviors of rod-coil block molecules on solid supports, such as their morphologies, structures, and molecular alignments, is still lacking.…”
Section: Introductionmentioning
confidence: 99%